2001
DOI: 10.1161/hh2201.100315
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Channels Mediate Ca 2+ Influx and Contraction in Rat Pulmonary Artery

Abstract: Abstract-Cation channels activated by Ca 2ϩ store depletion have been proposed to mediate Ca 2ϩ influx in vascular smooth muscle cells. The aim of this study was to determine if store-operated channels have a functional role in pulmonary artery smooth muscle cells (PASMCs). In intact rat pulmonary artery rings, cyclopiazonic acid (CPA) produced a sustained contraction that was resistant to inhibition by nifedipine, but abolished in Ca 2ϩ -free solution and 50% blocked in the presence of 6 mol/L Cd 2ϩ , 10 mol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
194
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(220 citation statements)
references
References 44 publications
22
194
1
3
Order By: Relevance
“…To determine if a similar mechanism operates in ASM, on-cell measurements of single channel currents were conducted both prior to and during passive store depletion with either CPA or BAPTA-AM. In all cell-attached patches examined, there was evidence of spontaneous single channel activity (,44% exhibiting robust activity), which was inhibit CPA-activated membrane currents and/or CCE in several tissues [16,21,27]. In the present study, application of 10 and 100 mM La 3+ reversibly inhibited the BAPTA-AMevoked current in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…To determine if a similar mechanism operates in ASM, on-cell measurements of single channel currents were conducted both prior to and during passive store depletion with either CPA or BAPTA-AM. In all cell-attached patches examined, there was evidence of spontaneous single channel activity (,44% exhibiting robust activity), which was inhibit CPA-activated membrane currents and/or CCE in several tissues [16,21,27]. In the present study, application of 10 and 100 mM La 3+ reversibly inhibited the BAPTA-AMevoked current in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…CPA enhances Ca 2+ entry in several other ASM preparations presumably through activation of Ca 2+ -permeable NSCCs [10,15,16,24]. Basal NSCC currents have also been described in isolated smooth muscle cells from rabbit portal vein [25], ear artery [26] and coronary artery [22] as well as rat pulmonary artery [27].…”
Section: Discussionmentioning
confidence: 93%
“…Functional TRPC channels exist in native cells as homo-or heterotetramers composed of two or more TRPC subunits (29,42,43). Studies have shown that overexpression of TRPC genes in mammalian cells leads to the formation of Ca 2ϩ permeable cation channels activated by both ligand-receptor interaction and store depletion (29,31,33,(42)(43)(44)(45)(46)(47)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…A central aspect of pulmonary vascular remodeling is medial hypertrophy caused by sustained pulmonary vasoconstriction (2-4), excessive pulmonary artery smooth muscle cell (PASMC) proliferation (5), and inhibited PASMC apoptosis (6, 7), resulting in a narrowed vascular lumen and increased PVR. Although its etiology remains unclear, elevated levels of circulating mitogens, dysfunction or down-regulation of receptors and ion channels, upregulation of transporters, and heightened activity of elastases and glycoproteins have been implicated in IPAH (5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Transient receptor potential (TRP) channel genes may encode subunits that form receptor-(ROC) and store-(SOC) operated Ca 2ϩ channels in many cell types, including PASMC and pulmonary artery endothelial cells (PAEC) (28,(30)(31)(32)(33)(34). Ca 2ϩ entry through ROC and SOC increases [Ca 2ϩ ] cyt , allowing for phosphorylation of signal transduction proteins and transcription factors (23,24,(35)(36)(37)(38), that are essential for the progression of the cell cycle (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation